Atomistic Origin of Rate-Dependent Serrated Plastic Flow in Metallic Glasses - Yao YG; Jiang SY; Jiang MQ; Dai LH (Nanoscale Research Letters, 2008)
Abstract Nanoindentation simulations on a binary metallic glass were performed under various strain rates by using molecular dynamics. The rate-dependent serrated plastic flow was clearly observed, and the spatiotemporal behavior of its underlying irreversible atomic rearrangement was probed. Our findings clearly validate that the serration is a temporally inhomogeneous characteristic of such rearrangements and not directly dependent on the resultant shear-banding spatiality. The unique spatiotemporal distribution of shear banding during nanoindentation is highlighted in terms of the potential energy landscape (PEL) theory.